The Joy of X: A Guided Tour of Mathematics, from One to Infinity - Steven H Strogatz (Atlantic Books, 2012)
Award-winning Steven Strogatz, one of the foremost popularisers of maths, has written a witty and fascinating account of maths\' most compelling ideas and how, so often, they are an integral part of everyday life. How should you flip your mattress to get the maximum wear out of it? How many people should you date before settling down? How does Google search the internet? Why does the stock market swing so often, and so wildly? Maths is everywhere, often where we don\'t even realise. Award-winning professor Steven Strogatz acts as our guide as he takes us on a tour of numbers that - unbeknownst to the unitiated - connect pop culture, literature, art, philosophy, current affairs, business and even every day life. In \The Joy of X\, Strogatz explains the great ideas of maths - from negative numbers to calculus, fat tails to infinity - with clarity, wit and insight. He is the maths teacher you never had and this book is perfect for the smart and curious, the expert and the beginner. It is suitable for readers of Ian Stewart\'s Professor Stewart\'s \Cabinet of Mathematical Curiosities\, Alex Bellos\' \Alex\'s Adventures in Numberland\, Marcus de Sautoy\'s \The Number Mysteries\.